Inhibition of DHCR24 activates LXRα to ameliorate hepatic steatosis and inflammation - Enchen Zhou; Xiaoke Ge; Hiroyuki Nakashima; Rumei Li; Hendrik J P van der Zande; Cong Liu; Zhuang Li; Christoph Müller; Franz Bracher; Yassene Mohammed; Jan Freark de Boer; Folkert Kuipers; et al. (EMBO Molecular Medicine)
Abstract Liver X receptor (LXR) agonism has theoretical potential for treating NAFLD/NASH, but synthetic agonists induce hyperlipidemia in preclinical models. Desmosterol, which is converted by Δ24‐dehydrocholesterol reductase (DHCR24) into cholesterol, is a potent endogenous LXR agonist with anti‐inflammatory properties. We aimed to investigate the effects of DHCR24 inhibition on NAFLD/NASH development. Here, by using APOE*3‐Leiden. CETP mice, a well‐established translational model that develops diet‐induced human‐like NAFLD/NASH characteristics, we report that SH42, a published DHCR24 inhibitor, markedly increases desmosterol levels in liver and plasma, reduces hepatic lipid content and the steatosis score, and decreases plasma fatty acid and cholesteryl ester concentrations. Flow cytometry showed that SH42 decreases liver inflammation by preventing Kupffer cell activation and monocyte infiltration. LXRα deficiency completely abolishes these beneficial effects of SH42. Together, the inhibition of DHCR24 by SH42 prevents diet‐induced hepatic steatosis and inflammation in a strictly LXRα‐dependent manner without causing hyperlipidemia. Finally, we also showed that SH42 treatment decreased liver collagen content and plasma alanine transaminase levels in an established NAFLD model. In conclusion, we anticipate that pharmacological DHCR24 inhibition may represent a novel therapeutic strategy for treatment of NAFLD/NASH.